بوابة اتحاد المكتبات الجامعية المصرية ودورها في إتاحة خدمات المعلومات للباحثين بجامعة بني سويف: دراسة حالة - محمد، آمال طه Mohammed, Amal Taha (جامعة بني سويف - كلية الآداب, 2016)
أصبح استخدام الإنترنت وكل ما يطرح عليها من مستجدات أمرا مهما لمنتجي ومسوقي خدمات الإنترنت والمستخدمين النهائيين أيضا ولا شك أن ما يعرف بالبوابات أصبحت من المواقع الشاملة التي يهتم المنتجون والمسوقون للمعلومات بتطويرها باستمرار بما يعمق تسهيل وسرعة الاستخدام من جانب المستفيدين وتقديم خدمات معلوماتية أفضل. ولا شك أن المكتبات الجامعية تمثل أحد أهم أنواع المكتبات كما أنها بمثابة القلب للجامعة حيث تمثل عنصرا أساسيا في العملية التعليمية والبحثية وبالتالي فإن دراسة بواباتها على الإنترنت لا يقل أهمية عن دراستها في الواقع حيث تمثل الواجهة الأساسية التي يتعامل معها الباحثون بشكل مباشر في الجامعات ومراكز المعلومات للحصول على متطلباتهم من مصادر المعلومات ذات الثقة. وتهدف هذه الدراسة إلى: التعريف ببوابات الإنترنت بشكل عام ودورها في إتاحة خدمات المكتبات والمعلومات. وكذلك التعريف ببوابة اتحاد مكتبات الجامعات المصرية، وطرق الدخول لها على الإنترنت. ثم تحليل موقع اتحاد المكتبات الجامعية المصرية وما يوفره من خدمات معلومات. للباحثين بجامعة بني سويف فيما يتعلق بالحصول على المعلومات المرتبطة ببحوثهم وكافة خدمات المعلومات المتعلقة بهذا الأمر.
The use of the Internet and all what is put on the latest developments becomes an important thing for the producers and marketers of Internet services and the final-users also. no doubt that portals is comprehensive sites aproducesr and information marketers are interested by Developed it continuously including deepens facilitate and speed of the use by the beneficiaries and the provision of better information service. There is no doubt that the academic libraries represents one of the most important types of libraries and it is the heart of the university as an essential element in the educational process, research, and thus the study of its portals on the Internet is not of less importance than studied in fact represent the basic interface with the researchers directly in the universities and information centers for their relevant sources of information confidence. the aim of this study was to: - Definition Internet portals in general and its role in providing library services and information. - Definition of the portals of Egyptian university library consortium and ways to engage on the Internet - Analysis the site of the Egyptian university library consortium and the information services that produce .for the Researchers at the Beni Suef University and all information services help them.
Keywords: المكتبات الجامعية -- نظم المعلومات -- الفهارس الآلية -- خدمات المعلومات -- اختزان واسترجاع المعلومات -- مصر